Bioremediasi Tanah Tercemar Menggunakan Bakteri Escherichia Coli di TPA Mandala Tegal Sari Medan - Atika Puspita (CV.ITTC INDONESIA, 2023)
The increasing amount of polluted land is a factor of environmental damage. Waste management that causes environmental damage. One option to overcome this problem is to carry out bioremediation techniques on polluted soil, which means improving the environment using microorganisms. This research was conducted to obtain the morphology of Escherichia coli bacteria. from landfills. The technique used in this study uses the ex-situ technique. This soil sampling method is carried out in a configurational manner to obtain an overview (unbiased estimate) of the microbial attributes in a relatively homogeneous area or plot.